«Греческое» и «варварское» в Северо-Западном Причерноморье в «переходный» период (в связи с исследованием погребений конца VI – первой половины V вв. до н.э. у с. Маяки) - Носова, Л.В. (Материалы по археологии Северного Причерноморья, 2011)
The period of the second half of 6th - the beginning of 5th centuries BC was a 4transition one* in the history of European Scythians. It was a period of becoming of 4Classical Scythia*, of transformation of the culture of Pontic nomads, related to the appearance of new nomadic groups from the East. It is possible to designate one hypothetical marker of this «transitional* nomadic wave— cruciform plates with zoomorphic compositions. «New* Scythians of the first wave (the second half of 6th century BC) were divided: one part went away westward, the other remained in the Black Sea region and was «built in* the tribal hierarchical structure, which had been formed in the region. «Old Scythia* already was not able to control all of territory, but the dynasty of the earlier period remained ahead at least until the fin of 6th century BC. The «headquarters* of newcomers settled in the Dnieper Left-Bank forest- steppe, and some nomad groups stayed in the Steppe, in particular, in the Lower Bug area and the Lower Dniester one. The author supposes that the «new* Scythians of the first wave resided in the localities of the Greek colonies of Northwestern Black Sea coast. It is possible that the recent investigated graves on the East Bank of Lower Dniester have been made by nomads allied with Nikonion (as the early tumulus cemetery in the territory of Olbiopoleis — by nomads allied with Olbia). Approximately, in the second quarter of the 5th century, the situation was changed. New nomadic groups arrived to in the North Black Sea region. The former tribal structure was finally destroyed. A new page in the history of the North Black Sea region is related to the Ariapeithes' dynasty, to Herodotus' Scythia.